Turkey’s National Interest in The Civil War in Libya for The Period 2019-2020 - Mohammad Naufal Eprillian Salsabil (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Civil War that took place in Libya in 2011, where the uprising carried out by the Libyan people against the regime of Muammar Khadafi and triggered by a series of events in the Middle East or better known as the "Jasmine Revolution" (The act of overthrowing the ruling rulers who were considered too authoritarian; Jasmine as a symbol of chastity has a fragrant aroma. The fallen demonstrators are considered sacred, whose blood is fragrant, supposed to be jasmine). During the conflict, there were several countries involved in the Libyan civil war, one of which was Turkey, which carried out its national interests there. The purpose of this study is to analyze why Turkey became involved in the civil war in Libya after the Muammar Khadaffi era. This research uses descriptive qualitative research methods that are implemented with theories in the study of International Relations. Qualitative research has the benefit of gaining an understanding of the opinions, reasons and motivations underlying an event which in this study is in the form of Turkey's National Interest in the Civil War in Libya. The result of this research is that Turkey wants to realize its national interests, especially in terms of economic interests. Turkey's national interests in terms of economy include: wanting to control the oil and gas resources found in the Mediterranean Sea. Turkey wants to conduct gas exploration along the Turkish and Libyan border in the northeastern part of the Mediterranean. The 200-mile sea border will be Turkey's gas exploration ground. In addition, there are business interests where Turkey exports goods worth US$ 2 billion annually. As a result of the ongoing conflict in Libya, it suffered losses of US $19 Billion.